824 A cross country analysis of drowning in Sri Lanka: 2001 to 2006 and 2009. (1st September 2016) - Matthews, Bernadette; Birch, Rhiannon; Jayawardena, Mevan; Mathew, Dushani; Nanayakkara, Asanka; Wiyayaratne, Sanath; Dharmaratne, Samath D
Abstract : Introduction: Drowning is a major cause of death and injury in Sri Lanka. Published data on the number and causes of drowning incidents of provinces are scarce. Therefore, we conducted this analysis to describe the burden of drowning in Sri Lanka from 2001 to 2006 and 2009 by province. Methods: Data from the first drowning report, 'Drowning prevention report Sri Lanka', published in December, 2014 by the Life Saving Association of Sri Lanka and Life Saving Victoria was used in this analysis. This report includes unintentional drowning deaths reported in Sri Lanka during the study period. Results: Sri Lanka consists of nine provinces, with the North Central being the largest (16% of total area) and the Western the smallest (5.6% of total area). The highest proportion of the population (28.6%) live in the Western province and the smallest in the Northern province (5.6%). Each year, an estimated 236 people die in the Western province from drowning while 44 die in the Uwa and the Northern provinces. The death rate is highest in the North Western province (6.3 per 100, 000) and lowest in the Central province (3.4 per 100, 000). North Western (6.3), North Central (5.4) and Southern (4.2) provinces had a higher drowning death rate than the national average (4.4 per 100, 000). Even in some of the provinces adjoining the ocean (Eastern and Northern), the commonest location of drowning was reportedly lakes and wells. Conclusion: Significant cross country differences identified in this analysis should be used by policy makers to prevent deaths from drowning in Sri Lanka.